Blood Pressure, Heart Rate, and CNS Stimulant Medication Use in Children with and without ADHD: Analysis of NHANES Data - Hailpern, Susan M.; Egan, Brent M.; Lewis, Kimberly D.; Wagner, Carol; Shattat, Ghassan F.; Al Qaoud, Doaa I.; Shatat, Ibrahim F. (Frontiers in Pediatrics, 2014)
It is estimated that 2-3% of children in the US have hypertension (HTN) and 8% of children ages 4-17 carry the diagnosis of Attention Deficit Hyperactivity Disorder (ADHD). The prevalence of HTN and cardiovascular (CV) risk factors in children with ADHD on CNS stimulant treatment (stimulants) compared to no treatment and compared to their healthy counterparts is not well described. Using NHANES data, we examined demographic, BP and CV risk factors of 4,907 children aged 12-18 years with and without the diagnosis of ADHD, and further examined the CV risk in a subgroup of ADHD patients on stimulants. 383 (10.7%) children were reported to have ADHD; of whom 111 (3.4%) were on stimulants. Children with ADHD on stimulants were significantly younger, male, and white compared to those with ADHD not on medication and those without ADHD. BMI, eGFR, cholesterol, the prevalence of albuminuria and poverty were not significantly different between the three groups. 160 (2.7%) had BP in the hypertensive and 637 (12.4%) in the prehypertensive range. The prevalence of elevated BP (HTN and/or pre-HTN range) was not different between children with ADHD on stimulants compared to ADHD without medication and those without ADHD. Heart Rate (HR) was significantly higher in the ADHD group on stimulants vs. the groups ADHD on no stimulants and without ADHD. When the relationship between stimulants and the risk of abnormal BP was examined, there was a significant interaction between having BP in the HTN range and sex. After adjusting for BMI, race and age, females with ADHD on stimulants tended to be older and had significantly more BP in the hypertensive range. On the other hand, males were more likely to be of a white race and older, but not hypertensive. Children with ADHD on stimulants have significantly higher HR than children with ADHD on no stimulants and children without ADHD. On the other hand, the prevalence of abnormal BP classification is comparable between the three groups.